Analysis of the determinants of alcohol consumption and expenditure in Ecuador: an econometric analysis - Ricardo Yajamín-Villamarín; Ricardo Yajamín-Villamarín (Frontiers in Public Health, 2025)
BackgroundThis study delves into the determinants of alcohol consumption and expenditure in Ecuador, focusing on personal characteristics, education levels, and regional variations. This study aimed to provide nuanced insights into alcohol-related behaviors within the Ecuadorian population.MethodsEmploying probit and Tobit models, the study ensures a robust analytical framework to assess the factors influencing alcohol consumption and expenditure. Data were collected from the 2014 Survey of Living Conditions, spanning urban and rural areas of Ecuador, guaranteeing a diverse population representation. The study includes individuals from random households, totaling 66,418 individuals over 18 years. Employing various measurements, including the use of a probit model for alcohol consumption and a Tobit model for alcohol expenditure, the study considers key variables such as smoking, gender, age, employment status, and regional location, contributing to a detailed understanding of alcohol-related behaviors.ResultsFor female individuals, there is a negative association, decreasing the probability of alcohol consumption by 6.6% (p-value: 0.000). Conversely, being a smoker exhibits a positive association, increasing the likelihood by 10.2% (p-value: 0.000). Regarding alcohol expenditure, being female is linked to a reduction in spending by $0.885 (p-value: 0.000). Being a smoker reveals an increase in spending by $0.914 (p-value: 0.000). Regional variations, education level, and employment status play crucial roles in shaping alcohol-related behaviors.ConclusionThis research provides nuanced insights into the socioeconomic determinants of alcohol-related behaviors in Ecuador. The findings underscore the necessity for targeted public policies, including gender-specific interventions, anti-smoking strategies, and considerations for regional variations.